Efeitos do treinamento multicomponente sobre a memória de reconhecimento e parâmetros oxidativos hipocampais em ratas submetidas à privação maternal - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The brain is a structure that begins its development in the intrauterine period and remains developing after birth, being vulnerable to external influences in the first years of life. Neonatal stress is one of the external influences that can negatively influence the Nervous System development, promoting short- and long-term alterations. The maternal separation (MS) is an animal model that allows the investigation of disorders related to early life stress, promoting neuroanatomical, neurochemistry, and behavioral alterations that persist throughout life. The combination of exercises, including physical and cognitive, called multicomponent training (MT), has presented benefits in studies with older adults, but its effects on MS-related alterations are still unclear. The present study aimed to investigate the effects of MT on recognition memory and hippocampal oxidative parameters in female rats submitted to SM. The MS protocol was performed for ten days, except in the control groups. The MT groups performed the MT protocol for six weeks in adult life, consisting of the alternate practice of running, strength, and cognitive exercises. The recognition memory of the animals was evaluated using the object recognition task (OR). The hippocampal reactive oxygen species (ROS), lipid peroxidation, and total antioxidant capacity were evaluated. The MS females did not present OR memory deficits, demonstrating that, unlike males, MS did not interfere with the females’ recognition memory. The MS increased the hippocampal ROS levels and decreased the total antioxidant capacity in the hippocampus. MT was able to reverse these effects, promoting the decrease of ROS and the increase of total antioxidant capacity in the hippocampus. MT presents a potential to manage alterations in the oxidative balance related to neonatal stress.
Effects of multicomponent training on recognition memory and hippocampal oxidative parameters in rats subjected to maternal deprivation
Keywords: Estresse neonatal; Exercício físico; Object recognition; Hippocampus; Physical exercise; Cognitive exercise; Hipocampo; Neonatal stress; Exercício cognitivo; Reconhecimento de objetos; CNPQ::CIENCIAS BIOLOGICAS